G-C3N4 / Ag-coated NiBx photocatalytic material with high hydrogen production activity and preparation method of g-C3N4 / Ag-coated NiBx photocatalytic material
By depositing NiBx by Ag-induced autocatalytic deposition on the surface of g-C3N4 photocatalyst, the Ag@NiBx core-shell cocatalyst is formed, and the photocatalyst with low activity in the hydrogen production process is solved, and a photocatalytic material with high hydrogen production activity is achieved.
Patent Information
- Application Number
- CN202411978836.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing photocatalysts show poor activity in photocatalytic hydrogen production, mainly due to the recombination of photogenerated electron-hole pairs and the lack of effective hydrogen evolution active sites on the surface.
NiBx is deposited in situ on the surface of the g-C3N4 photocatalyst by Ag-induced autocatalytic deposition to form an Ag@NiBx core-shell cocatalyst with small size and uniform dispersion.
The photocatalytic hydrogen production activity is significantly improved. Compared with the g-C3N4/Ag material that is supported separately, its photocatalytic hydrogen production performance is higher, and the synthesis method is green and environmentally friendly and simple to operate.
Smart Images

Figure CN119680611A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalytic hydrogen production, and specifically relates to a g-C3N4 / Ag@NiB with high hydrogen production activity. x Photocatalytic material and preparation method thereof. Background Art
[0002] With the rapid consumption of fossil fuels, hydrogen, as a zero-pollution energy carrier, has become an ideal alternative to traditional carbon-based fuels due to its high energy density. The growing demand for hydrogen has promoted the development of photocatalytic water splitting technology, which can effectively convert renewable solar energy into hydrogen, showing good cost-effectiveness and environmental friendliness. However, for pure photocatalysts, such as the common graphite phase carbon nitride (g-C3N4), photogenerated electron-hole pairs are easily recombinated during the photocatalytic hydrogen production process, and its surface lacks effective hydrogen evolution active sites, which ultimately leads to single-phase g-C3N4 showing poor photocatalytic hydrogen evolution activity. Therefore, in order to solve the problem of low photocatalytic hydrogen production performance, the photocatalyst needs to be modified.
[0003] Co-catalyst modification is to combine the co-catalyst with the main photocatalyst material to promote the photocatalytic reaction. It is widely considered to be one of the effective methods to improve the performance of photocatalytic hydrogen production. Generally speaking, the co-catalyst itself does not have photocatalytic properties, but after a very small amount of co-catalyst is modified on the main photocatalyst material, it can promote the directional migration of photogenerated carriers, thereby improving the performance of the photocatalytic material. Not only that, the introduction of the co-catalyst can make it a more effective active site for catalytic reactions, further promoting the catalytic performance of the photocatalyst. Precious metals, especially platinum, are widely considered to be the most effective co-catalysts in photocatalytic hydrogen evolution due to their excellent carrier transport properties and suitable hydrogen adsorption strength. However, considering the extreme scarcity of precious metal resources, researchers have developed some low-cost and abundant materials, such as metal sulfides, carbides, selenides and phosphides, as alternatives to co-catalysts for photocatalytic hydrogen production. However, the above-mentioned transition metal compounds often exhibit semiconductor properties, and their own electrical conductivity is not high, which inhibits their photocatalytic activity to a certain extent. In recent years, transition metal borides, especially NiB x , due to its special metal-like conductivity and adjustable composition, it has been widely used in the field of catalysis. Therefore, it has a high potential application in photocatalytic hydrogen production.
[0004] When NiB x When NiB is modified on the surface of photocatalyst g-C3N4 for photocatalytic hydrogen production, its photogenerated electron transfer efficiency is crucial to improve its photocatalytic hydrogen production activity. xThe particles should be small in size and tightly combined with the g-C3N4 main material surface, and evenly distributed without agglomeration. x The main synthesis methods include liquid molten salt method, solid double decomposition method, metal thermal reduction method, and room temperature liquid phase chemical reduction method. Most of these methods require very high temperatures and are not suitable for mild photocatalysis. Therefore, among the above methods, room temperature chemical reduction method is the mainstream synthesis method of nickel boride additives in the field of photocatalysis. However, the current chemical reduction method based on sodium borohydride will cause the reaction to occur quickly due to its strong reducing property, and the resulting NiB x It shows serious agglomeration phenomenon, which is not conducive to catalytic reaction. Therefore, it is necessary to develop a NiB suitable for photocatalysis. x A room temperature mild synthesis method with additives to obtain small size and uniformly dispersed NiB x However, to the best of our knowledge, there are no related reports in this regard. Summary of the invention
[0005] The technical problem to be solved by the present invention is to propose a simple preparation method of Ag-induced autocatalytic deposition in view of the above-mentioned prior art. This method anchors Ag and in-situ autocatalytically deposits NiB on its surface. x , Ag@NiB with small size and uniform dispersion was obtained x Core-shell co-catalyst with excellent photocatalytic hydrogen production activity.
[0006] A g-C3N4 / Ag@NiB with high hydrogen production activity x The method for preparing a photocatalytic material comprises the following steps:
[0007] S1. Under strong stirring conditions, add 0.1 g of g-C3N4 solid powder to 80 mL of triethanolamine aqueous solution. After uniform dispersion, add 1 mL of silver nitrate solution to obtain a uniform suspension.
[0008] S2, removing oxygen from the suspension, and subjecting the suspension to photodeposition treatment in a nitrogen atmosphere for 1 hour; after the reaction, centrifuging, washing and drying are performed in sequence to obtain a g-C3N4 / Ag product;
[0009] S3, the g-C3N4 / Ag product was dispersed in 80 mL of deionized water, and 1 mL of nickel acetate-dimethylammonium borane mixed solution was added under stirring and nitrogen atmosphere to carry out Ag-induced autocatalytic deposition reaction to obtain g-C3N4 / Ag@NiB x Photocatalyst.
[0010] Furthermore, in S1, the concentration of the triethanolamine aqueous solution is 10 vol%, and the concentration of the silver nitrate solution is 0.03 mol / L.
[0011] Furthermore, in S2, the photodeposition is performed under the irradiation of 420 nm visible light.
[0012] Further, in S3, the concentration of dimethylamine borane in the nickel acetate-dimethylamine borane mixed solution is 0.01-2.00 mol / L.
[0013] Further, in S3, the concentration of nickel acetate in the nickel acetate-dimethylamine borane mixed solution is 0.01-2.00 mol / L.
[0014] Furthermore, in S3, the temperature of the deionized water is 0-90°C.
[0015] Further, in S3, the self-deposition reaction time is 5-120 min.
[0016] The g-C3N4 / Ag@NiB prepared by the above method x Photocatalytic materials.
[0017] The above g-C3N4 / Ag@NiB x Application of photocatalytic materials in the field of hydrogen production photocatalysts.
[0018] The beneficial effects of the present invention are as follows:
[0019] The present invention proposes g-C3N4 / Ag@NiB with high hydrogen production activity x A simple synthesis method of photocatalytic materials, including the initial photodeposition of Ag nanoparticles and the subsequent Ag-induced NiB x The in-situ autocatalytic deposition process finally obtains Ag@NiB with core-shell structure uniformly dispersed on the surface of g-C3N4 photocatalytic host material. x The catalyst was used as a promoter to finally obtain g-C3N4 / Ag@NiB with high hydrogen production activity. x Photocatalytic materials. g-C3N4 / Ag@NiB prepared by this method x The photocatalytic material has higher photocatalytic hydrogen production activity than the g-C3N4 / Ag material loaded with Ag alone. The synthesis method is green and environmentally friendly, simple to operate, requires low equipment, and is expected to produce good social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described below in conjunction with the accompanying drawings.
[0021] Figure 1 The g-C3N4 / Ag@NiB with high hydrogen production activity in Example 1 x Preparation routes of photocatalytic materials;
[0022] Figure 2 The g-C3N4 / Ag@NiB with high hydrogen production activity in Example 1 x TEM and EDS-Mapping images of photocatalytic materials;
[0023] Figure 3 For g-C3N4 and g-C3N4 / Ag@NiB in Example 1 x XRD pattern of
[0024] Figure 4 For g-C3N4 and g-C3N4 / Ag@NiB in Example 1 x Infrared spectrum of
[0025] Figure 5 For g-C3N4, g-C3N4 / Ag and g-C3N4 / Ag@NiB in Example 1 x UV-visible diffuse reflectance absorption spectrum;
[0026] Figure 6 For g-C3N4 and g-C3N4 / Ag@NiB in Example 1 x XPS spectrum of
[0027] Figure 7 For g-C3N4, g-C3N4 / Ag and g-C3N4 / Ag@NiB in Example 1 x Photocatalyst hydrogen production performance;
[0028] Figure 8 The g-C3N4 / Ag@NiB with high hydrogen production activity in Example 1 x Cyclic photocatalytic activity of photocatalytic materials. DETAILED DESCRIPTION
[0029] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0030] In the present invention, the crystal structure and phase composition information of the material are analyzed by X-ray diffraction (XRD) spectroscopy;
[0031] Use X-ray diffraction (XRD) spectroscopy to analyze the crystal structure and phase composition information of the material;
[0032] The morphology and structure of the materials were observed using a transmission electron microscope (TEM);
[0033] Infrared spectroscopy is used to analyze the structure and composition information of materials;
[0034] Use X-ray photoelectron spectroscopy (XPS) to detect the chemical element composition and valence state of the material surface;
[0035] Use UV-vis diffuse reflectance to test the optical properties of materials.
[0036] The first thing to be protected in the present invention is a g-C3N4 / Ag@NiB with high hydrogen production activity. x The method for preparing a photocatalytic material comprises the following steps:
[0037] 1) respectively preparing a silver nitrate aqueous solution with a concentration of 0.03 mol / L and a nickel acetate-dimethylamine borane mixed aqueous solution with a certain concentration. In the nickel acetate-dimethylamine borane mixed solution, the concentration of nickel acetate is 0.01-2.00 mol / L, and the best concentration of nickel acetate is 0.05-0.50 mol / L; the concentration of dimethylamine borane is 0.01-2.00 mol / L, and the best concentration of dimethylamine borane is 0.05-0.50 mol / L.
[0038] 2) Under strong stirring, 0.1 g of g-C3N4 solid powder was added to 80 mL of triethanolamine aqueous solution (10 vol%) to form a uniformly dispersed suspension, and then 1 mL of silver nitrate solution was added thereto. The stirring speed was 500 r / min and the stirring time was 15 min.
[0039] 3) The suspension obtained in step 2) is passed through high-purity N2 to remove O2 in the air, and then photodeposition is performed under 420nm visible light irradiation for 1 hour. The obtained sample is centrifuged, washed, and dried to obtain g-C3N4 / Ag.
[0040] 4) The g-C3N4 / Ag obtained in step 3) is dispersed in deionized water at a certain temperature, and 1 mL of the nickel acetate-dimethylamine borane mixed solution in step 1) is added under continuous stirring and N2 atmosphere. At this time, the Ag nanoparticles can in-situ catalyze the reaction of nickel acetate and dimethylamine borane, and in-situ self-deposit NiB on the surface of the Ag nanoparticles. x , and obtain g-C3N4 / Ag@NiB x Photocatalyst, self-deposition reaction time is 30-60min.
[0041] The present invention proposes g-C3N4 / Ag@NiB with high hydrogen production activity x A simple preparation method of photocatalytic materials: First, Ag nanoparticles are uniformly deposited on the g-C3N4 main material by photodeposition to obtain g-C3N4 / Ag. In the mixed solution of nickel acetate and dimethylamine borane, dimethylamine borane is a weakly reducing organic boron source and is difficult to directly react with Ni. 2+ When g-C3N4 / Ag is dispersed in the above solution, the Ag nanoparticles on g-C3N4 have a catalytic effect, which spontaneously induces dimethylamine borane to react with Ni2+ Reaction, in situ deposition of NiB on Ag nanoparticles x . Due to NiB x The formation of Ag@NiB was achieved by anchoring Ag nanoparticles uniformly dispersed on g-C3N4, and finally core-shell Ag@NiB was obtained on g-C3N4. x Promoter catalyst.
[0042] The second thing to be protected in the present invention is the g-C3N4 / Ag@NiB obtained by the above preparation method. x Photocatalytic materials.
[0043] The third thing to be protected in the present invention is g-C3N4 / Ag@NiB x Application of photocatalytic materials in hydrogen production. Specifically, g-C3N4 / Ag@NiB x The photocatalytic hydrogen production performance of the photocatalytic material was evaluated by decomposing water under visible light to produce hydrogen. The detailed experimental process is as follows: g-C3N4 / Ag@NiB synthesized by the method of the present invention was x The photocatalyst (0.05 g) was dispersed in a flat-bottomed three-necked flask containing 80 mL of triethanolamine sacrificial agent (10 vol%), and then nitrogen was introduced for 15 minutes to remove oxygen from the reaction system. Finally, the photocatalytic hydrogen production reaction was carried out under stirring and illumination. In the above-mentioned photocatalytic hydrogen production experiment, 4 LED lamps (3 W, 420 nm) were used as the irradiation source. Every 1 hour, 400 μL of gas was extracted with a trace gas injector and injected into a gas chromatograph (Shimadzu, GC-14C, Japan) to detect the hydrogen content.
[0044] <Example 1>
[0045] A g-C3N4 / Ag@NiB with high hydrogen production activity x The method for preparing a photocatalytic material comprises the following steps:
[0046] (1) 0.1 g of g-C3N4 solid powder was dispersed in 80 mL of triethanolamine aqueous solution (10 vol%) to form a uniform suspension;
[0047] (2) Under stirring, 1 mL of silver nitrate solution (0.03 mol / L) was added to the above suspension system, nitrogen was passed through for 15 min, and then irradiated under 420 nm visible light for 1 h to uniformly photodeposit Ag nanoparticles on the surface of g-C3N4 to obtain a g-C3N4 / Ag product;
[0048] (3) The obtained g-C3N4 / Ag product (0.1 g) was uniformly dispersed in 25°C deionized water (80 mL), and then 1 mL of a mixed solution of nickel acetate (0.08 mol / L) and dimethylamine borane (0.40 mol / L) was added dropwise to the above suspension under continuous N2 atmosphere. After the autocatalytic deposition reaction for 1 h, the reaction product was centrifuged, washed, and dried in sequence to finally obtain g-C3N4 / Ag@NiB x Photocatalytic materials.
[0049] Figure 1 For this example, g-C3N4 / Ag@NiB x Preparation process of photocatalytic materials.
[0050] Figure 2 For this example, g-C3N4 / Ag@NiB x TEM image of photocatalytic material and corresponding EDS-Mapping image. Figure 2 It can be clearly seen in a that the g-C3N4 photocatalytic main material is a very thin nanosheet morphology, and there are many dark and evenly distributed small particles on its surface, which can be attributed to the Ag@NiB x Nanoparticles. After further enlarging these small particles, Figure 2 b can see Ag@NiB x The nanoparticles have a distinct core-shell structure with a size of 3-5 nm, and lattice fringes with a spacing of 0.24 nm can be observed, corresponding to the Ag (111) plane, while the NiB x The above Ag@NiB x The structure of the nanoparticles can be further analyzed by Figure 2 c-c5 to prove that it is a core-shell structure.
[0051] Figure 3 In this example, g-C3N4 and g-C3N4 / Ag@NiB x From the XRD spectrum, it can be clearly seen that the g-C3N4 sample has an obvious characteristic peak at 27.4 degrees, which corresponds to the interlayer stacking of g-C3N4 nanosheets. x The samples showed interlayer stacking peaks of the same intensity at the same position, proving that the core-shell Ag@NiB x The additive loading method is relatively mild and will not change the intrinsic crystal structure of g-C3N4.
[0052] Figure 4In this example, g-C3N4 and g-C3N4 / Ag@NiB x From the infrared spectrum, it can be found that g-C3N4 has a peak at 810cm -1 There is a characteristic peak at 1200-1600cm -1 There are multiple continuous peaks near 3000-3200cm -1 The characteristic peak corresponding to the terminal NH appeared in the range. Compared with g-C3N4, the g-C3N4 / Ag@NiB modified by the additive x The same infrared characteristic peaks indicate that the additives are deposited on the surface of g-C3N4 through this method without changing the internal structure of g-C3N4.
[0053] Figure 5 In this example, g-C3N4 (a), g-C3N4 / Ag (b) and g-C3N4 / Ag@NiB x (c) UV-visible diffuse reflectance absorption spectra of photocatalytic materials. Compared with pure g-C3N4, all samples modified with additives showed enhanced light absorption in the visible light region. In addition, it can be seen from the figure that at around 480nm, g-C3N4 / Ag and g-C3N4 / Ag@NiB x There is an obvious absorption peak, which is attributed to the local surface plasmon resonance effect (LSPR) of Ag nanoparticles, indicating the successful deposition of Ag nanoparticles. The successful deposition of the above co-catalyst can also be proved by the change of sample color (inset).
[0054] Figure 6 In this example, g-C3N4 and g-C3N4 / Ag@NiB x High-resolution XPS spectra of C1s (a), Ag 3d (b), Ni 2p (c) and B1s (d). It can be seen from the figure that compared with g-C3N4, g-C3N4 / Ag@NiB x The CN peak of Ag@NiB x There is an electron transfer effect between the additive and the g-C3N4 main material, proving that Ag@NiB x The additives are densely deposited on g-C3N4. In addition, g-C3N4 / Ag@NiB x Obvious characteristic peaks of Ag, Ni and B elements appeared, which further proved that g-C3N4 / Ag@NiB x Successful synthesis of photocatalyst.
[0055] Figure 7In this embodiment, g-C3N4, g-C3N4 / Ag and g-C3N4 / Ag@NiB x Photocatalytic hydrogen production performance of photocatalytic materials. It can be seen that the photocatalytic hydrogen production performance of pure g-C3N4 is basically zero. When Ag is deposited on g-C3N4, the photocatalytic hydrogen production performance of g-C3N4 / Ag is 47 μmol h -1 g -1 After the self-catalytic deposition to form the core-shell additive, g-C3N4 / Ag@NiB x The photocatalytic hydrogen production performance of the photocatalytic material was further significantly enhanced, reaching 298 μmol h -1 g -1 .
[0056] Figure 8 This is the g-C3N4 / Ag@NiB with high hydrogen production activity in this example. x The cyclic stability of hydrogen production performance of photocatalytic materials. Figure 8 It can be seen that after four cycles of photocatalytic hydrogen production experiments, g-C3N4 / Ag@NiB x The photocatalytic hydrogen production activity of the photocatalyst did not decrease significantly, indicating that the high-activity g-C3N4 / Ag@NiB prepared by the present invention x The material has good cycle stability in photocatalytic hydrogen production applications.
[0057] <Example 2>
[0058] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the nickel acetate concentration is 0.01 mol / L.
[0059] <Example 3>
[0060] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the nickel acetate concentration is 0.05 mol / L.
[0061] <Example 4>
[0062] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the nickel acetate concentration is 0.50 mol / L.
[0063] <Example 5>
[0064] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the nickel acetate concentration is 2.00 mol / L.
[0065] The g-C3N4 / Ag@NiB prepared in Example 2-5 xThe photocatalytic hydrogen production performance of the g-C3N4 / Ag@NiB was tested. Combined with the test results of Example 1, it was found that when the nickel acetate concentrations were 0.01, 0.05, 0.08, 0.50, and 2.00 mol / L, respectively. x The photocatalytic hydrogen production performance is 158, 291, 298, 290 and 239 μmol h -1 g -1 From the results, it can be seen that no matter how much the concentration of nickel acetate is added, g-C3N4 / Ag@NiB x The photocatalytic hydrogen production of g-C3N4 / Ag is always higher than that of g-C3N4 / Ag, and its performance increases first and then decreases with the increase of nickel acetate concentration. x During the preparation of the photocatalyst, the optimal concentration of nickel acetate solution is 0.05-0.50 mol / L.
[0066] <Example 6>
[0067] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the concentration of dimethylamine borane is 0.01 mol / L.
[0068] <Example 7>
[0069] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the concentration of dimethylamine borane is 0.05 mol / L.
[0070] <Example 8>
[0071] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the concentration of dimethylamine borane is 0.50 mol / L.
[0072] <Example 9>
[0073] The difference between this embodiment and embodiment 1 is that in the nickel acetate-dimethylamine borane mixed solution, the concentration of dimethylamine borane is 2.00 mol / L.
[0074] The g-C3N4 / Ag@NiB prepared in Examples 6-9 x The photocatalytic hydrogen production performance of the material was tested. Combined with the test results of Example 1, it was found that when the concentrations of dimethylamine borane were 0.01, 0.05, 0.40, 0.50 and 2.00 mol / L, g-C3N4 / Ag@NiB x The photocatalytic hydrogen production performance is 142, 285, 298, 286 and 220 μmol h -1 g -1 Therefore, in g-C3N4 / Ag@NiBx During the preparation of the photocatalyst, the optimal concentration of dimethylamine borane solution is 0.05-0.50 mol / L.
[0075] <Example 10>
[0076] The difference between this embodiment and embodiment 1 is that in step 3), the temperature of the deionized water is 0°C.
[0077] <Example 11>
[0078] The difference between this embodiment and embodiment 1 is that in step 3), the temperature of the deionized water is 15°C.
[0079] <Example 12>
[0080] The difference between this embodiment and embodiment 1 is that in step 3), the temperature of the deionized water is 50°C.
[0081] <Example 13>
[0082] The difference between this embodiment and embodiment 1 is that in step 3), the temperature of the deionized water is 90°C.
[0083] g-C3N4 / Ag@NiB prepared in Examples 10-13 x The photocatalytic hydrogen production performance of the material was tested. Combined with the test results of Example 1, it was found that when the temperature of the deionized water was 0, 15, 25, 50 and 90 °C, the g-C3N4 / Ag@NiB x The photocatalytic hydrogen production performance is 182, 288, 298, 295 and 254 μmol h -1 g -1 From the results, it can be seen that when the temperature of deionized water is low, the reaction is incomplete, while when the temperature is high, the NiB x Agglomeration may occur, resulting in reduced performance. x During the preparation of the photocatalyst, the optimal deionized water temperature is 15-50°C.
[0084] <Example 14>
[0085] The difference between this embodiment and embodiment 1 is that in step 3), the self-deposition reaction time is 5 minutes.
[0086] <Example 15>
[0087] The difference between this embodiment and embodiment 1 is that in step 3), the self-deposition reaction time is 30 minutes.
[0088] <Example 16>
[0089] The difference between this embodiment and embodiment 1 is that in step 3), the self-deposition reaction time is 90 minutes.
[0090] <Example 17>
[0091] The difference between this embodiment and embodiment 1 is that in step 3), the self-deposition reaction time is 120 minutes.
[0092] g-C3N4 / Ag@NiB prepared in Examples 14-17 x The photocatalytic hydrogen production performance of the material was tested. Combined with the test results of Example 1, it was found that when the self-deposition time was 5, 30, 60, 90 and 120 min, the obtained g-C3N4 / Ag@NiB x The photocatalytic hydrogen production performance is 105, 290, 298, 293 and 292 μmol h -1 g -1 From the results, it can be seen that when the self-deposition reaction time is 5 minutes, the hydrogen production performance test result is low because the reaction is not complete. When the reaction time is extended to 30-120 minutes, g-C3N4 / Ag@NiB x The hydrogen production performance of g-C3N4 / Ag@NiB x During the preparation of the photocatalyst, the optimal self-deposition time is 30-60 minutes.
[0093] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A g-C3N4 / Ag@NiB with high hydrogen production activity x The method for preparing a photocatalytic material is characterized in that: The following steps are involved: S1. Under strong stirring conditions, add 0.1 g of g-C3N4 solid powder to 80 mL of triethanolamine aqueous solution. After uniform dispersion, add 1 mL of silver nitrate solution to obtain a uniform suspension. S2, removing oxygen from the suspension, and subjecting the suspension to photodeposition treatment in a nitrogen atmosphere for 1 hour; after the reaction, centrifuging, washing and drying are performed in sequence to obtain a g-C3N4 / Ag product; S3, the g-C3N4 / Ag product was dispersed in 80 mL of deionized water, and 1 mL of nickel acetate-dimethylammonium borane mixed solution was added under stirring and nitrogen atmosphere to carry out Ag-induced autocatalytic deposition reaction to obtain g-C3N4 / Ag@NiB x Photocatalyst, wherein the amount of g-C3N4 / Ag product used is 0.1g.
2. The g-C3N4 / Ag@NiB with high hydrogen production activity according to claim 1 x The method for preparing a photocatalytic material is characterized in that: In S1, the concentration of the triethanolamine aqueous solution is 10 vol%, and the concentration of the silver nitrate solution is 0.03 mol / L.
3. The g-C3N4 / Ag@NiB with high hydrogen production activity according to claim 1 x The method for preparing a photocatalytic material is characterized in that: In S2, the photodeposition is performed under the conditions of 420 nm visible light irradiation.
4. The g-C3N4 / Ag@NiB with high hydrogen production activity according to claim 1 x The method for preparing a photocatalytic material is characterized in that: In S3, the concentration of dimethylamine borane in the nickel acetate-dimethylamine borane mixed solution is 0.01-2.00 mol / L.
5. The g-C3N4 / Ag@NiB with high hydrogen production activity according to claim 1 x The method for preparing a photocatalytic material is characterized in that: In S3, the concentration of nickel acetate in the nickel acetate-dimethylamine borane mixed solution is 0.01-2.00 mol / L.
6. The g-C3N4 / Ag@NiB with high hydrogen production activity according to claim 1 x The method for preparing a photocatalytic material is characterized in that: In S3, the temperature of the deionized water is 0-90°C.
7. The g-C3N4 / Ag@NiB with high hydrogen production activity according to claim 1 x The method for preparing a photocatalytic material is characterized in that: In S3, the time of the autocatalytic deposition reaction is 5-120 min.
8. g-C3N4 / Ag@NiB obtained by the preparation method according to any one of claims 1 to 7 x Photocatalytic materials.
9. g-C3N4 / Ag@NiB as claimed in claim 8 x Application of photocatalytic materials in the field of hydrogen production photocatalysts.
Citation Information
Patent Citations
Catalyst for catalytically hydrolyzing sodium borohydride to prepare hydrogen and preparation method thereof
CN102029159A
Nano silver catalyst for catalyzing hydrolysis of amino borane and preparation method thereof
CN103934003A
Preparation and application of graphite phase carbon nitride nanosheet loaded silver monatomic photocatalyst
CN114682286A
Catalyst and its prepn process and use
CN1440925A
Method for manufacture and coating of nanostructured components
US20100215915A1